A modified cellulose urushiol-based water-based composite coating and preparation method thereof

By introducing modified nanocellulose into uucol-based aqueous polymers, hydrogen bonding or covalent bonding with nanocellulose is used to form a three-dimensional network structure, and the paint film has low hardness. The problem of this has achieved significant improvement in the hardness of the paint film and improvement in adhesion.

CN116836595BActive Publication Date: 2025-02-14RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310528978.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2025-02-14
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

The paint film of uuol-based aqueous polymers is relatively hard and difficult to meet certain application needs.

Method used

Modified nanocellulose is formed by introducing silanol or silanol oligomers on the surface of the nanocellulose and covalently grafting or crosslinking reaction with the uucol-based aqueous polymer by mixing ultrasonic treatment to form modified nanocellulose and dispersing them evenly in In the uugol-based aqueous polymer, a three-dimensional network structure is formed to increase the hardness of the paint film.

Benefits of technology

The hardness of the paint film is significantly improved, up to 6H, and the binding force of the modified nanocellulose and uugol-based aqueous polymer is enhanced, improving the adhesion of the paint film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116836595B_ABST
    Figure CN116836595B_ABST
Patent Text Reader

Abstract

The present invention provides a modified cellulose urushiol-based water-based composite coating and a preparation method thereof, comprising preparing an urushiol-based water-based polymer, preparing modified nanocellulose and preparing an urushiol-based water-based composite coating. The present invention introduces silanol or silanol oligomers on the surface of nanocellulose, and the silanol or silanol oligomers act as a bridge to perform covalent grafting or cross-linking reaction with the urushiol-based water-based polymer, and the modified nanocellulose can be uniformly dispersed in the urushiol-based water-based polymer, so that the modified nanocellulose and the urushiol-based water-based polymer form a three-dimensional network structure, thereby improving the hardness of the paint film, and the maximum hardness can reach 6H.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a modified cellulose urushiol-based water-based composite coating and a preparation method thereof. Background Art

[0002] Natural lacquer has a long history of use in my country and its resources are abundant. The lacquer film has excellent properties of toughness, wear resistance, high gloss, thermal stability, water resistance and chemical resistance, but its high viscosity, poor construction and harsh film-forming conditions limit the wide application of lacquer.

[0003] With the advancement of science and technology, water-based paints have emerged. Water-based paints have the advantages of no pollution to the environment, low price, not easy to powder, and convenient construction, which greatly expands the application range of paints. Among them, urushiol-based water-based polymers are the most widely used, but urushiol-based water-based polymers still have the problem of low paint film hardness. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] The invention provides a modified cellulose urushiol-based water-based composite coating and a preparation method thereof, so as to solve the technical problem of how to improve the hardness of urushiol-based water-based polymer paint film.

[0006] (II) Technical solution

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a modified cellulose urushiol-based water-based composite coating, which comprises the following steps:

[0008] S1. Preparation of urushiol-based waterborne polymer

[0009] The urushiol, epibromopropane, a phase transfer catalyst and a sodium hydroxide solution are mixed and chemically reacted to obtain urushiol glycidyl ether; the urushiol glycidyl ether, polyethylene glycol and sodium hydroxide are mixed and phase inversion reaction is performed to obtain an urushiol-based emulsifier; the urushiol-based emulsifier, a polyvinyl alcohol solution, urushiol and a distilled water solution are blended to obtain an urushiol-based waterborne polymer;

[0010] S2. Preparation of modified nanocellulose

[0011] Using silanol and / or silanol oligomer as a modifier, mixing with nanocellulose and distilled water and subjecting to ultrasonic treatment, so that the hydroxyl groups in the silanol and / or silanol oligomer are hydrogen-bonded or covalently bonded with the hydroxyl groups on the surface of the nanocellulose, thereby obtaining modified nanocellulose;

[0012] S3. Preparation of urushiol-based water-based composite coating

[0013] The modified nanocellulose is dispersed in distilled water to obtain a modified cellulose dispersion; the modified cellulose dispersion is blended with an urushiol-based aqueous polymer solution to obtain a modified nanocellulose urushiol-based aqueous composite coating.

[0014] Furthermore, in step S1, urushiol, epibromopropane and a phase transfer catalyst are mixed for a ring-opening reaction, and sodium hydroxide is added dropwise to the ring-opening reaction product to perform a ring-closing reaction to obtain urushiol glycidyl ether; the mass ratio of urushiol, epibromopropane and phase transfer catalyst is (83-87):220:1.7; the ring-opening reaction temperature is 98-102°C, and the ring-opening reaction time is 2-3h; the mass concentration of sodium hydroxide solution is 33-37%, and the mass ratio of sodium hydroxide in urushiol and sodium hydroxide solution is 85:(18-20); the dropping rate of sodium hydroxide solution is 1-4 drops / min, and the temperature of the reaction system is 49-50°C during the dropping; the ring-closing reaction temperature is 63-67°C, and the ring-closing reaction time is 2.8-3.2h.

[0015] Furthermore, in step S1, when the phase inversion reaction is carried out, the mass ratio of urushiol glycidyl ether, polyethylene glycol and sodium hydroxide is 1:(1.3-1.7):0.077, the phase inversion reaction temperature is 88-92°C, and the phase inversion reaction time is 15-30 min; the mass concentration of the polyvinyl alcohol solution is 4.8-5.2%, the mass concentration of the urushiol-based emulsifier, polyvinyl alcohol solution, urushiol and distilled water is (0.38-0.42):16:12:1, and the diameter of the emulsion particles in the urushiol-based aqueous polymer is less than 1 μm.

[0016] Furthermore, in step S2, the mixed ultrasonic treatment includes the following steps: (1) mixing the silane coupling agent and distilled water for hydrolysis, wherein the hydrolysis product is silanol, and part of the silanol forms silanol oligomers through self-polymerization to obtain a silanol and / or silanol oligomer solution; (2) dispersing the nanocellulose in distilled water and mixing it with the silanol and / or silanol oligomer solution; and (3) subjecting the mixed solution to ultrasonic treatment.

[0017] Furthermore, in step S2, the mass concentration of the silanol and / or silanol oligomer solution is 0.15-0.16%; the volume ratio of the mass of nanocellulose to the silanol and / or silanol oligomer solution is (0.3-0.4 g):(100-120 mL); the ultrasonic power during ultrasonic treatment is 1200 W, and the ultrasonic time is 20-30 min.

[0018] Furthermore, in step S2, the mass ratio of nanocellulose to modifier is 9:5.

[0019] Furthermore, in step S2, the diameter of the nanocellulose is 4-5 nm, and the aspect ratio is 2000-2500.

[0020] Further, in step S2, the silane coupling agent includes 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane.

[0021] Furthermore, in step S3, the mass ratio of the modified nanocellulose to the urushiol-based aqueous polymer is (0.015-0.06):100; and the mass percentage of the modified cellulose in the modified cellulose dispersion is 0.28-0.32%.

[0022] In addition, the present invention also provides a modified cellulose urushiol-based water-based composite coating, which is prepared by the above method.

[0023] (III) Beneficial effects

[0024] The present invention provides a modified cellulose urushiol-based water-based composite coating and a preparation method thereof, comprising preparing an urushiol-based water-based polymer, preparing modified nanocellulose and preparing an urushiol-based water-based composite coating. The present invention introduces silanol or silanol oligomers on the surface of nanocellulose, and the silanol or silanol oligomers act as a bridge to perform covalent grafting or cross-linking reaction with the urushiol-based water-based polymer, and the modified nanocellulose can be uniformly dispersed in the urushiol-based water-based polymer, so that the modified nanocellulose and the urushiol-based water-based polymer form a three-dimensional network structure, thereby improving the hardness of the paint film, and the maximum hardness can reach 6H. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The XRD spectra of nanocellulose, modified nanocellulose, urushiol-based waterborne polymer and urushiol-based waterborne composite coating are shown in Figure 1. In the figure, a is the XRD spectrum of nanocellulose, b is the XRD spectrum of modified nanocellulose, c is the XRD spectrum of urushiol-based waterborne polymer, and d is the XRD spectrum of urushiol-based waterborne composite coating. In the figure, the abscissa is 2θ, in degrees, and the ordinate is intensity, in au.

[0026] Figure 2 is the XPS spectrum of modified nanocellulose; Figure 2A For low-resolution scanned images, Figure 2B This is the high-resolution scanning spectrum after C1s fitting in modified nanocellulose (a is the OCC diffraction peak, b is the CO diffraction peak, and c is the CC diffraction peak). Figure 2C This is a high-resolution optical scanning spectrum after Si 2p fitting in modified nanocellulose (a is the Si-O-Si diffraction peak, b is the SiO3 diffraction peak). In the figure, the horizontal axis is the binding energy, the unit is eV, and the vertical axis is the intensity, the unit is au. DETAILED DESCRIPTION

[0027] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.

[0028] The present invention provides a method for preparing a modified cellulose urushiol-based water-based composite coating, which comprises the following steps:

[0029] S1. Preparation of urushiol-based waterborne polymer

[0030] The urushiol, epibromopropane, a phase transfer catalyst and a sodium hydroxide solution are mixed and subjected to a chemical reaction to obtain urushiol glycidyl ether; the urushiol glycidyl ether, polyethylene glycol and sodium hydroxide are mixed and subjected to a phase inversion reaction to obtain a urushiol-based emulsifier; the urushiol-based emulsifier, a polyvinyl alcohol solution, urushiol and a distilled water solution are blended to obtain a urushiol-based waterborne polymer.

[0031] In the present invention, the structure of urushiol is shown in the following formula:

[0032]

[0033] Wherein, R is an alkane, alkene, conjugated or non-conjugated diene or triene containing C15 to C17.

[0034] Preferably, the phase transfer catalyst is benzyltriethylammonium chloride, and the reaction equation of the chemical reaction is as shown below:

[0035]

[0036] In the present invention, when the chemical reaction is carried out, urushiol, epibromopropane and a phase transfer catalyst are mixed to carry out a ring-opening reaction, and sodium hydroxide is added dropwise to the ring-opening reaction product to carry out a ring-closing reaction to obtain urushiol glycidyl ether.

[0037] The reaction equation of the ring-opening reaction is shown below:

[0038]

[0039] The mass ratio of urushiol, epibromopropane and phase transfer catalyst is (83-87):220:1.7; the ring-opening reaction temperature is 98-102°C, and the ring-opening reaction time is 2-3h.

[0040] Preferably, the mass ratio of urushiol, epibromopropane and phase transfer catalyst is 85:220:1.7; the ring-opening reaction temperature is 99-100° C., and the ring-opening reaction time is 2.5-2.8 h.

[0041] After the ring-opening reaction is completed, sodium hydroxide solution is added dropwise to the product of the ring-opening reaction to perform a ring-closing reaction. The equation for the ring-closing reaction is shown below:

[0042]

[0043] The mass concentration of the sodium hydroxide solution is 33-37%, the mass ratio of urushiol to the sodium hydroxide in the sodium hydroxide solution is 85:(18-20); the dropping rate of the sodium hydroxide solution is 1-4 drops / min, and the temperature of the reaction system is 49-50° C. during the dropping; the closed-loop reaction temperature is 63-67° C., and the closed-loop reaction time is 2.8-3.2 h.

[0044] Preferably, the mass concentration of the sodium hydroxide solution is 34-35%, the mass ratio of urushiol to sodium hydroxide in the sodium hydroxide solution is 85:(18.9-19.5); the dropping rate of the sodium hydroxide solution is 2-3 drops / min; the ring-closing reaction temperature is 64-65° C., and the ring-closing reaction time is 2.9-3.0 h.

[0045] After the ring-closing reaction, the process further includes: adjusting the pH value of the ring-closing reaction product to neutral and then performing reduced pressure distillation. The pH value can be adjusted by mixing the ring-closing reaction product with water and then performing liquid separation; removing the aqueous phase after liquid separation, and repeating the liquid separation operation if the pH value of the oil phase has not yet reached neutrality. The present invention has no particular limitation on the number of repetitions, as long as neutrality can be achieved. The reduced pressure distillation temperature is 60 to 80° C., and the reduced pressure distillation time is 1 to 3 hours. The present invention can recover excess epibromopropane and water through reduced pressure distillation.

[0046] Preferably, the vacuum distillation temperature is 65-70° C., and the vacuum distillation time is 2-2.5 h.

[0047] In the present invention, the equation of the phase inversion reaction is as shown below:

[0048]

[0049] When the phase inversion reaction is carried out, the mass ratio of urushiol glycidyl ether, polyethylene glycol and sodium hydroxide is 1:(1.3-1.7):0.077, the phase inversion reaction temperature is 88-92° C., and the phase inversion reaction time is 15-30 min.

[0050] Preferably, the polyethylene glycol is polyethylene glycol 4000, the mass ratio of urushiol glycidyl ether, polyethylene glycol and sodium hydroxide is 1.0:1.5:0.077, the phase inversion reaction temperature is 89-90° C., and the phase inversion reaction time is 20-30 min.

[0051] When the solutions are blended, the mass concentration of the polyvinyl alcohol solution is 4.8-5.2%, the mass concentrations of the urushiol-based emulsifier, the polyvinyl alcohol solution, the urushiol and distilled water are (0.38-0.42):16:12:1, and the diameter of the emulsion particles in the urushiol-based water-based polymer is less than 1 μm.

[0052] Preferably, the mass concentration of the polyvinyl alcohol solution is 4.9-5.0%, the mass concentration of the urushiol-based emulsifier, polyvinyl alcohol solution, urushiol and water is 0.4:16:12:1, and the diameter of the emulsion particles in the urushiol-based aqueous polymer is 0.5-0.8 μm.

[0053] The invention has the limitation that demulsification and stratification will not occur after the urushiol-based water-based polymer is centrifuged, the centrifugal speed is 3000 r / min, and the centrifugal time is 15 min.

[0054] S2. Preparation of modified nanocellulose

[0055] Silanol and / or silanol oligomer are used as modifiers, mixed with nanocellulose and distilled water, and ultrasonically treated, so that the hydroxyl groups in the silanol and / or silanol oligomer are hydrogen-bonded or covalently bonded with the hydroxyl groups on the surface of the nanocellulose to obtain modified nanocellulose.

[0056] The mixed ultrasonic treatment comprises the following steps: (1) mixing a silane coupling agent and distilled water for hydrolysis, wherein the hydrolysis product is silanol, and part of the silanol forms silanol oligomers through self-polymerization, thereby obtaining a silanol and / or silanol oligomer solution; (2) dispersing nanocellulose in distilled water and mixing it with the silanol and / or silanol oligomer solution; and (3) subjecting the mixed solution to ultrasonic treatment.

[0057] The product after ultrasonic treatment is subjected to solid-liquid separation, the solid is taken, and after solid-liquid separation, it is dried to obtain modified nanocellulose.

[0058] The mass concentration of the silanol and / or silanol oligomer solution is 0.15-0.16%; the volume ratio of the mass of nanocellulose to the silanol and / or silanol oligomer solution is (0.3-0.4g):(100-120mL); the ultrasonic power during ultrasonic treatment is 1200W, and the ultrasonic time is 20-30min; the mass ratio of nanocellulose to modifier is 9:5; the diameter of the nanocellulose is 4-5nm, and the aspect ratio is 2000-2500.

[0059] Preferably, the nanocellulose is biomass cellulose, and the raw materials for preparing the biomass cellulose preferably include peanut shells or biostraw. The modifier is obtained by hydrolyzing a silane coupling agent. The silane coupling agent includes 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane. The silane coupling agent is hydrolyzed to obtain silanols, and part of the silanols obtained by hydrolysis self-polymerize to form silanol oligomers, and the degree of polymerization of the silanol oligomers is 2 to 10.

[0060] The hydroxyl groups in the silanol and / or silanol oligomers hydrogen bond or covalently bond with the hydroxyl groups on the surface of the nanocellulose to obtain modified nanocellulose, the structural formula of which is shown below:

[0061]

[0062] S3. Preparation of urushiol-based water-based composite coating

[0063] The modified nanocellulose is dispersed in distilled water to obtain a modified cellulose dispersion; the modified cellulose dispersion is blended with an urushiol-based aqueous polymer solution to obtain a modified nanocellulose urushiol-based aqueous composite coating.

[0064] The mass ratio of modified nanocellulose and urushiol-based aqueous polymer is (0.015-0.06):100; the mass percentage of modified cellulose in the modified cellulose dispersion is 0.28-0.32%; the stirring speed during blending is 1000-3000 r / min, and the stirring time is 2.8-3.2 h.

[0065] Preferably, the mass ratio of modified cellulose to urushiol-based aqueous polymer is (0.03-0.045):100; the mass percentage of modified cellulose in the modified cellulose dispersion is 0.29-0.3%; the stirring speed is 2000-2500 r / min, and the stirring time is 2.9-3.0 h.

[0066] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0067] Example 1

[0068] S1. Preparation of urushiol-based waterborne polymer

[0069] 85g of urushiol, 220g of epichlorohydrin and 1.7g of triethylammonium chloride were mixed and subjected to ring-opening reaction at 100°C for 3h; the reaction system was cooled to 50°C, and 54g of a sodium hydroxide solution with a mass concentration of 35% was added dropwise to the reaction system within 2h; after the addition was completed, the ring-closing reaction was carried out at 65°C for 3h; the ring-closing reaction product was mixed with water for separation, and the pH value of the ring-closing reaction product was neutral, and then vacuum distilled (65°C, 1h) was carried out to recover excess epichlorohydrin and water to obtain urushiol glycidyl ether;

[0070] 15 g of polyethylene glycol (PEG4000), 10 g of urushiol glycidyl ether and 0.77 g of sodium hydroxide were mixed and subjected to phase inversion reaction at 90° C. for 30 min to obtain an urushiol-based emulsifier;

[0071] 0.4 g of urushiol-based emulsifier, 16 g of 5% polyvinyl alcohol solution, 12 g of urushiol and 1 mL of distilled water were mixed to obtain an urushiol-based waterborne polymer;

[0072] S2. Preparation of modified nanocellulose

[0073] 0.192 mL of 3-aminopropyltriethoxysilane and 120 mL of distilled water were stirred at a speed of 2000 r / min for 15 min to obtain a silanol and / or silanol oligomer solution with a mass concentration of 0.16%;

[0074] The silanol and / or silanol oligomer solution was mixed with 100.36 g of nanocellulose aqueous dispersion (biomass cellulose prepared from peanut shells had a diameter of 4 nm, an aspect ratio of 2500, and a mass ratio of nanocellulose to water of 0.3:100) under stirring for 3 h, and then ultrasonically treated for 30 min at a power of 1200 W to obtain a modified nanocellulose suspension (the mass percentage of modified nanocellulose was 0.3%).

[0075] S3. Preparation of urushiol-based water-based composite coating

[0076] According to the mass ratio of the modified nanocellulose suspension and the urushiol-based aqueous polymer of 0.05:100, the modified nanocellulose suspension and the urushiol-based aqueous polymer were mixed at a speed of 2000 r / min for 3 h, and placed in an ultrasonic grinder for ultrasonic treatment (ultrasonic power 1000 W, ultrasonic time 30 min).

[0077] Example 2

[0078] The lacquer phenol-based water-based composite coating was prepared according to the method of Example 1, except that the mass ratio of the modified nanocellulose suspension to the lacquer phenol-based water-based polymer was 1:100, and the coating was subjected to high-speed magnetic stirring at a speed of 1000 r / min at room temperature for 3 h, and then placed in an ultrasonic pulverizer for ultrasonic treatment (ultrasonic power 1500 W, ultrasonic time 30 min).

[0079] Example 3

[0080] The lacquer phenol-based water-based composite coating was prepared according to the method of Example 1, except that the mass ratio of the modified nanocellulose suspension to the lacquer phenol-based water-based polymer was 1.5:100, and the coating was subjected to high-speed magnetic stirring at 3000 r / min at room temperature for 3 h, and then placed in an ultrasonic mill for ultrasonic treatment (ultrasonic power 3000 W, ultrasonic time 30 min).

[0081] Example 4

[0082] The lacquer phenol-based water-based composite coating was prepared according to the method of Example 1, except that the mass ratio of the modified nanocellulose suspension to the lacquer phenol-based water-based polymer was 2:100, and the coating was subjected to high-speed magnetic stirring at a speed of 4000 r / min at room temperature for 3 h, and then placed in an ultrasonic mill for ultrasonic treatment (ultrasonic power 5000 W, ultrasonic time 30 min).

[0083] Comparative Example 1

[0084] The urushiol-based waterborne polymer prepared in Example 1 was used as a comparative example.

[0085] The nanocellulose, modified nanocellulose, urushiol-based waterborne polymer and urushiol-based waterborne composite coating in Example 1 were subjected to XRD detection to obtain XRD spectra, such as Figure 1 As shown. Figure 1 It can be seen that the modification of nanocellulose by silane coupling agent only occurs on the surface of nanocellulose and does not destroy the crystalline region inside nanocellulose. It is very important to ensure that the crystalline region of nanocellulose is not destroyed during the modification of nanocellulose for nanocellulose to enhance organic polymers. If the crystalline region of nanocellulose is destroyed, resulting in a decrease in crystallinity, it will seriously affect the effect of nanocellulose on the film hardness enhancement of urushiol-based waterborne composite coatings. Compared with urushiol-based waterborne polymers, the sharp diffraction peak of urushiol-based waterborne composite coating samples at 16.4° indicates that urushiol-based waterborne composite coatings have higher crystallinity than urushiol-based waterborne polymer samples. This may be because the modified cellulose, as a nucleating agent, promotes the heterogeneous nucleation of urushiol-based waterborne polymers on the surface of modified cellulose and further induces their crystallization.

[0086] The modified cellulose in Example 1 was subjected to XRS detection to obtain an XPS spectrum, as shown in FIG2 . Figure 2A It can be seen that in addition to the C and O elements in the modified nanocellulose, there are also Si and N elements belonging to the silane coupling agent. Figure 2B and 2C It can be seen that the modified nanocellulose contains Si-O-Si (101.5 eV) and SiO3 (103.62 eV) bonds, which is because the hydrolysis product of the silane coupling agent is coated on the cellulose surface. It can be seen that the silane coupling agent undergoes hydrolysis reaction to form silanols, some of which undergo self-polymerization to form silanol oligomers, and the hydroxyl groups on the surfaces of the other part of the silanols and silanol oligomers undergo hydrogen bonding or chemical bonding with the hydroxyl groups on the surface of the cellulose to form modified cellulose.

[0087] According to GB 23999-2009, the lacquer phenol-based water-based composite coatings prepared in Examples 1 to 4 and the lacquer phenol-based water-based polymer of Comparative Example 1 were coated on a clean glass sheet or tinplate and naturally cured at room temperature to form a film. The hardness, adhesion, glossiness and thickness of the paint film were tested. The results are listed in Table 1.

[0088] Table 1 Paint film properties obtained from the coatings of Examples 1 to 4 and Comparative Example 1

[0089] Serial number hardness Adhesion(grade) Glossiness(%) Film thickness (μm) Example 1 6H 1 38.70 16 Example 2 6H 1 34.20 16 Example 3 5H 3 34.10 20 Example 4 4H 4 20.70 20 Comparative Example 1 2H 6 16.90 30

[0090] It can be seen from the data in Table 1 that the paint film obtained by the lacquer phenol-based water-based composite coating prepared by the present invention has higher hardness and adhesion than the paint film obtained by the lacquer phenol-based water-based polymer. The paint film of the lacquer phenol-based water-based composite coating prepared by the present invention is more resistant to scratches, which indicates that the modified nanocellulose added as a nanofiller to the lacquer phenol-based water-based polymer can significantly improve the hardness and adhesion of the composite coating. The modified nanocellulose is uniformly dispersed in the lacquer phenol-based water-based polymer matrix, and the modified nanocellulose and the lacquer phenol-based water-based polymer form chemical bonds through the interaction between oxygen-containing polar groups (hydroxyl, carboxyl), thereby improving the hardness of the paint film; at the same time, the hydrogen bonds between several different polar groups existing in the metal substrate and the polar groups in the composite coating enhance the adhesion.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a modified cellulose urushiol-based water-based composite coating, characterized in that: The preparation method comprises the following steps: S1. Preparation of urushiol-based waterborne polymer The urushiol, epibromopropane and a phase transfer catalyst are mixed to carry out a ring-opening reaction, and sodium hydroxide is added dropwise to the ring-opening reaction product to carry out a ring-closing reaction to obtain urushiol glycidyl ether; the mass ratio of urushiol, epibromopropane and phase transfer catalyst is (83-87):220:1.7; the ring-opening reaction temperature is 98-102°C, and the ring-opening reaction time is 2-3h; the mass concentration of the sodium hydroxide solution is 33-37%, and the mass ratio of the sodium hydroxide in the urushiol and sodium hydroxide solution is 85:(18-20); the dropping rate of the sodium hydroxide solution is 1-4 drops / min, and the temperature of the reaction system during the dropping is 49-50°C; the ring-closing reaction temperature is 63-67°C, and the ring-closing reaction time is 2.8-3.2h; The urushiol glycidyl ether, polyethylene glycol and sodium hydroxide are mixed and phase inversion reaction is performed to obtain an urushiol-based emulsifier; during the phase inversion reaction, the mass ratio of the urushiol glycidyl ether, polyethylene glycol and sodium hydroxide is 1:(1.3-1.7):0.077, the phase inversion reaction temperature is 88-92°C, and the phase inversion reaction time is 15-30 min; the urushiol-based emulsifier, polyvinyl alcohol solution, urushiol and distilled water solution are blended to obtain an urushiol-based waterborne polymer; The mass concentration of the polyvinyl alcohol solution is 4.8-5.2%, the mass ratio of the urushiol-based emulsifier, the polyvinyl alcohol solution, the urushiol and the distilled water is (0.38-0.42):16:12:1, and the diameter of the latex particles in the urushiol-based water-based polymer is less than 1 μm; S2. Preparation of modified nanocellulose Silanol and silanol oligomers are used as modifiers, mixed with nanocellulose and distilled water, and ultrasonically treated, so that the hydroxyl groups in the silanol and silanol oligomers are hydrogen-bonded or covalently bonded with the hydroxyl groups on the surface of the nanocellulose to obtain modified nanocellulose; wherein, The mixed ultrasonic treatment comprises the following steps: (1) the silane coupling agent comprises 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane, the silane coupling agent and distilled water are mixed and hydrolyzed, the hydrolysis product is silanol, part of the silanol forms silanol oligomers through self-polymerization, and a silanol and silanol oligomer solution is obtained; (2) nanocellulose is dispersed in distilled water and mixed with the silanol and silanol oligomer solution; (3) the mixed solution is ultrasonically treated; the mass concentration of the silanol and silanol oligomer solution is 0.15-0.16%; the mass ratio of nanocellulose to the silanol and silanol oligomer solution is (0.3-0.4g):(100-120mL); the ultrasonic power during the ultrasonic treatment is 1200W, and the ultrasonic time is 20-30min; the mass ratio of nanocellulose to modifier is 9:5; the diameter of nanocellulose is 4-5nm, and the aspect ratio is 2000-2500; S3. Preparation of urushiol-based water-based composite coating The modified nanocellulose is dispersed in distilled water to obtain a modified cellulose dispersion; the modified cellulose dispersion is blended with an urushiol-based aqueous polymer solution to obtain a modified nanocellulose urushiol-based aqueous composite coating; wherein the mass ratio of the modified nanocellulose to the urushiol-based aqueous polymer is (0.015-0.06):100; and the mass percentage of the modified cellulose in the modified cellulose dispersion is 0.28-0.32%.

2. A modified cellulose urushiol-based water-based composite coating, characterized in that: The composite coating is prepared by the method as claimed in claim 1.

Citation Information

Patent Citations

  • Modified nanometer raw lacquer and preparation method thereof

    CN103589268A

  • Preparation method of urushiol glycidyl ether

    CN105820141A